2012
DOI: 10.7763/ijcea.2012.v3.176
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Particle Size Effect on Performance of Fluidized Bed Combustor Firing Ground Nutshells

Abstract: Biomass fuels come from many varieties of sources resulting in a wide range of sizes, physical and chemical properties. Among the technologies that can be used for biomass combustion, fluidized beds are emerging as the best due to their flexibility and high efficiency. The emissions from Fluidized Bed Combustor (FBC) are dependent on a number of operating conditions (temperature, excess air, fuel feed rate, etc) and fuel particle size. In the present work the effect of fuel particle size on emissions and over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The difference in particle size distribution of these wood fuels may have an influence on the combustion and pyrolysis process. For example, Suranani and Goli (2012) showed that the particle size of groundnut shells influenced burning performance in a fluidized bed combustor. They noted that maximum combustion efficiency was attained (89.5%) when pieces had an average size of 0.273 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in particle size distribution of these wood fuels may have an influence on the combustion and pyrolysis process. For example, Suranani and Goli (2012) showed that the particle size of groundnut shells influenced burning performance in a fluidized bed combustor. They noted that maximum combustion efficiency was attained (89.5%) when pieces had an average size of 0.273 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous research by Suranani and Goly [31], the size of fuel particles affects the amount of CO2 formed from combustion. Fuel with a smaller size tends to produce greater CO2 gas emissions, which indicates more complete combustion.…”
Section: Co2 Gas Emission Of Combustionmentioning
confidence: 99%
“…Therefore, only the H 2 inhibition effect was considered in this work since steam was used as the gasifying agent during the char conversion, i.e., the CO inhibition effect is negligible [30]. Since the size of the fuel particles was limited to between 125 and 500 µm, which is relatively small, the effect of the diffusion of oxygen was not taken into account in this study [35]. Langmuir-Hinshelwood/ Hougen-Watson (LHHW) models were used to interpret the conversion mechanism in this work since the models are applicable to describe char conversion in a mixture of steam, CO 2 , H 2 , and CO, which is the case in this study [34].…”
Section: Char Reactivity Modelsmentioning
confidence: 99%